(untitled) (Aporte Santiaguino, 2021)
The rocoto (Capsicum pubescens Ruiz & Pav.) is a nightshade with a center of origin in Peru, with great gastronomic value. It is affected by diseases that limit its development, spread by infected seeds. The in vitro culture of plant tissues allows the propagation of elite genotypes with the availability of pathogen-free plant material. The objective was to determine the in vitro response of hot pepper in the establishment of seeds and regeneration from terminal buds. Hot pepper seeds were used in different treatments with sodium hypochlorite. Leaves and roots of germinated rocotts were removed in vitro, leaving epicotyl with terminal buds and transferred to culture media with different concentrations of salts and MS vitamins for the in vitro regeneration phase, the organogenic response and oxidation were evaluated. In the establishment of hot pepper seeds, 100% disinfection was obtained using ethanol (70%) and sodium hypochlorite (2%) for 15 minutes, in the regeneration phase the culture medium with salts and MS vitamins at 100% concentration allowed to obtain 19.8% of organogenic response. The protocol for the in vitro establishment of hot pepper seeds was established and a low organogenic response was determined from terminal buds under in vitro conditions.